2019
DOI: 10.1101/19013193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multimodal neuroimaging and suicidality in a US population-based sample of school-aged children

Abstract: Importance: Suicide deaths and suicidality are considered a public health emergency, yet their brain underpinnings remain elusive. Objective: To examine individual, environmental, and clinical characteristics, as well as multimodal brain imaging correlates of suicidality in a US population-based sample of school-aged children. Design: Cross-sectional analysis of the first wave of data from the Adolescent Brain Cognitive Development study Setting: Multicenter population-based study Participants: Children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…The fMRI-based measures included did not seem to contribute to the classification of children with STB In contrast to these findings, previous studies have found that functional brain alterations in the prefrontal cortex are related to STB [20, 21] and contribute to the classification of suicidal youth [22]. However, our findings are consistent with a neuroimaging-specific evaluation of this same cohort, in which no association was found between suicidal thoughts and behaviors and functional neuroimaging measures [23]. These discrepant findings between ABCD and other studies could potentially be explained by the younger age of participants in the ABCD study, the fact that ABCD is a population study, or methodological issues that have been described elsewhere [24].…”
Section: Discussionsupporting
confidence: 78%
“…The fMRI-based measures included did not seem to contribute to the classification of children with STB In contrast to these findings, previous studies have found that functional brain alterations in the prefrontal cortex are related to STB [20, 21] and contribute to the classification of suicidal youth [22]. However, our findings are consistent with a neuroimaging-specific evaluation of this same cohort, in which no association was found between suicidal thoughts and behaviors and functional neuroimaging measures [23]. These discrepant findings between ABCD and other studies could potentially be explained by the younger age of participants in the ABCD study, the fact that ABCD is a population study, or methodological issues that have been described elsewhere [24].…”
Section: Discussionsupporting
confidence: 78%
“…A recent study that examined the association between STBs and brain structure in over 6,000 younger children aged 9-10 years in the Adolescent Brain Cognitive Development (ABCD) study did not reveal significant structural alterations on the frontal cortex in association with STBs (36).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, in the larger overall sample of this study, more substantial heterogeneity was introduced by including a variety of mental health conditions. A recent study that examined the association between STBs and brain structure in over 6,000 younger children aged 9-10 years in the Adolescent Brain Cognitive Development (ABCD) study did not reveal significant structural alterations on the frontal cortex in association with STBs (36). This may be related to the fact that the ABCD study is a general population sample with only a few children diagnosed with mood disorders, and STBs were less common and severe.…”
Section: Discussionmentioning
confidence: 99%
“…Important features in this model include white matter connectivity, morphometry, and functional connectivity within the distributed brain network, primarily the neocortex, including the inferior frontal gyrus, insula, and anterior cingulate cortex. The inferior frontal gyrus plays a role in emotional regulation, sustained attention, and language processing 34 , of which abnormalities were associated with suicidality in adolescents 35 . The insula and anterior cingulate cortex, as part of the salience network, are involved in the detection and integration of emotional and sensory stimuli 36 .…”
Section: Discussionmentioning
confidence: 99%